Integrating International Student Mobility in Work-Based Higher Education: The Case of Germany. (May 2017) - Graf, Lukas; Powell, Justin J. W.; Fortwengel, Johann; Bernhard, Nadine
Dual study programs are hybrid forms of work-based higher education that have expanded very rapidly in Germany—a country traditionally considered a key model in both higher education (HE) and vocational education and training (VET). The continued expansion of these hybrid programs increasingly raises questions if, how, and why they may be internationalized. Although comparative research suggests that this could be challenging due to the uniqueness of the German education and training system, strong forces support internationalization. This study examines the current state and the future prospects of internationalization of such innovative dual study programs by focusing on student mobility, a key dimension of internationalization. We find growing interest in but still relatively little mobility related to dual study programs, whether among German (outgoing) or international (incoming) students. Based on expert interviews and document analysis, we extend existing typologies of student mobility regarding specific features of work-based HE programs. Furthermore, we discuss opportunities—at home and abroad—for increasing student mobility in this rapidly expanding sector.